2021
DOI: 10.1002/wsb.1196
|View full text |Cite
|
Sign up to set email alerts
|

Application of Unmanned Aerial Vehicles and Thermal Imaging Cameras to Conduct Duck Brood Surveys

Abstract: Brood surveys are used to estimate productivity in ducks, but road‐side transects, aerial surveys, and double‐observer ground surveys have likely underestimated productivity. Duck broods are elusive and prefer wetlands with emergent vegetation where they hide at signs of disturbance, making it difficult to get accurate brood counts. Estimates of brood detection probabilities are typically below 50% and variable, which makes biological inferences about abundance tenuous. We conducted a study to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Previous studies using remote sensing found that vegetation cover type, sky condition, species, and survey altitude or GSD can all influence waterfowl detection within a survey area [20,[36][37][38][39]42,43]. Similarly, our results indicate that in UAS imagery, the waterfowl availability to be counted was strongly influenced by the combination of species, sex, vegetation cover type, and GSD.…”
Section: Availability Biassupporting
confidence: 76%
See 3 more Smart Citations
“…Previous studies using remote sensing found that vegetation cover type, sky condition, species, and survey altitude or GSD can all influence waterfowl detection within a survey area [20,[36][37][38][39]42,43]. Similarly, our results indicate that in UAS imagery, the waterfowl availability to be counted was strongly influenced by the combination of species, sex, vegetation cover type, and GSD.…”
Section: Availability Biassupporting
confidence: 76%
“…Overall, our results show that UASs, aerial imagery, artificial intelligence algorithms, and the use of correction factors may accurately estimate waterfowl abundance within single images across a wide range of environmental and flight conditions. Previous studies evaluating bird detection biases found that vegetation cover type, sky condition, species, and survey altitude or GSD can all influence bird detection within a survey area [20,[36][37][38][39]42,43]. We found that waterfowl availability bias was most influenced by environmental conditions, including vegetation cover type, GSD, and waterfowl characteristics, including species and sex, while perception bias was most influenced by GSD, affecting the probability of detecting birds, and vegetation-cover type, influencing the probability of algorithms generating false positives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IR sensor and processing technology has progressed and become more widely available since the timing of our surveys (2015–2016); thus, the monetary cost has possibly decreased. Unmanned aerial vehicles, or drones, are a cheaper platform for affixing IR cameras and IR surveys using drones have been widely tested with mixed results (Chrétien et al 2016, Beaver et al 2020, Bushaw et al 2021, Preston et al 2021). Drone flights are currently not practical in most feral horse and burro management areas however, because federal policy requires direct line of sight control of the aircraft (FAA 2021) which is difficult to achieve across these vast areas with rugged topography limiting vehicular access.…”
Section: Discussionmentioning
confidence: 99%